Buffer-gas-free mass-selective ion centering in Penning traps by simultaneous dipolar excitation of magnetron motion and quadrupolar excitation for interconversion between magnetron and cyclotron motion - Rosenbusch, Marco; Blaum, Klaus; Borgmann, Christopher; Kreim, Susanne (International journal of mass spectrometry, 2012)
A new excitation scheme of the radial ion-motional modes is introduced for Penning-trap ion-cyclotron-resonance experiments. By simultaneous dipolar excitation of the magnetron motion and resonant quadrupolar excitation for the conversion between magnetron motion and cyclotron motion, a mass-selective recentering of the ions of interest is performed while all other (contaminant) ions are ejected from the trap. This new technique does not rely on the application of a buffer gas as presently used [G. Savard, St. Becker, G. Bollen, H.-J. Kluge, R.B. Moore, Th. Otto, L. Schweikhard, H. Stolzenberg, U. Wiess, Physics Letters A 158 (1991) 247] and will thus prevent charge-exchange reactions and damping of the motion that decreases mass resolving power.